Current Opportunities and Future Prospects of Neuroprotective Therapy in Glaucoma. Literature Review. Part 2 - N. I. Kurysheva; A. V. Korneeva; S. I. Ponomareva; H. M. Plieva; V. E. Kim; I. D. Kim; M. V. Chebotareva (Oftalʹmologiâ)
This literature review is devoted to one of the most challenging problems of ophthalmology — neuroprotective and neuroregenerative treatment of glaucoma and consists of two parts. The second part of the review deals with the role of glia, inflammation and autoimmunization in the pathogenesis of neuroretinal degeneration in glaucoma optic neuropathy (GON), new treatment strategies based on modern achievements of gene and immunotherapy. Special attention is paid to promising therapeutic approaches based on artificial intelligence application, usage of peptide bioregulators, immunomodulators and mixed-action drugs. Alternative methods of axonal regeneration, including gene therapy and stem cell therapy, are discussed.